Agreement in Modern Standard Arabic constructions with cardinal numerals over ten - Michalski, Marcin (Lingua Posnaniensis, 2016)
In Modern Standard Arabic constructions with cardinal numerals over ten in which the noun denoting the counted object follows the numeral, e.g. al-ḫamsūna ǧundiyyan ‘the fifty soldiers’ (as opposed to al-ǧunūdu l-ḫamsūna ‘idem’), the noun is indefinite singular. When a property of the object counted is to be expressed by means of an attribute: an adjective, participle, or a relative clause, it agrees with the noun in gender, but agreement in the three remaining categories, i.e. number, case and definiteness, may be distributed between the noun and the numeral. The present study analyzes examples of such constructions found in contemporary journalistic texts. Four agreement configurations are distinguished, out of which three were described by Classical Arabic grammarians, while one is non-classical. In some instances, due to the syncretism of declension forms, agreement in case is indeterminate. The analysis of the examples shows that apart from variation in agreement that can be observed with some types of the qualifier, the choice of a particular agreement configuration depends on phraseology and/or the lexico-syntactic properties of the qualifier: whether it is a proper adjective, a nisba adjective, a participle, or a relative clause.